EMERGENCY DEPARTMENT AND INPATIENT CLINICAL DECISION TOOLS FOR THE MANAGEMENT OF FEBRILE YOUNG INFANTS AMONG TERTIARY PEDIATRIC CENTERS ACROSS CANADA. (18th May 2018) - Burstein, Brett; Gravel, Jocelyn; Aronson, Paul; Neuman, Mark
Abstract: BACKGROUND: With no nationally endorsed guidelines and newer diagnostic tools, there exists widespread practice variation in the management of febrile infants <90 days. OBJECTIVES: This study sought to evaluate the prevalence of clinical decision tools (CDTs) for the management of febrile young infants in the Emergency Department (ED) and inpatient settings among all tertiary paediatric centers across Canada. DESIGN/METHODS: A cross-sectional, Internet-based survey was distributed to both an ED and an inpatient physician representative at each of the 16 Canadian tertiary paediatric centers. Participants were asked to characterize their clinical settings, diagnostic test availability and institutional febrile young infant CDTs. Copies were requested of all febrile infant-specific materials for independent classification as clinical pathway, guideline or order set, and content review using list items determined a priori . The primary analysis was the proportion of settings that use a CDT for the management of febrile infants. Chi-square testing was used to compare proportions. RESULTS: Survey response rate was 100% (n = 32, 16 ED and 16 inpatient). Febrile young infant CDTs of any type were infrequently reported overall (9/32, 38%), and were more common in the ED than inpatient setting (50% vs. 6%, p=0.02). Prevalence of any CDT was not associated with hospital volume or physician training. Among EDs, clinical pathways, guidelines, and order sets were available at 6/16 (38%), 1/16 (6%), and 4/16 (25%) institutions, respectively. Among centers reporting existent CDTs, few reported ED or inpatient tracking of provider adherence or audits of impact (3/9, 33% overall). Review of existing CDTs revealed inter-center differences for inclusion ages, antibiotic treatment regimens, lumbar puncture recommendations, diagnostic testing and normal laboratory reference values. Despite wide availability reported at nearly all centers, C-reactive protein and respiratory viral testing were each rarely incorporated into existent CDTs (3/9, 33% for both). Procalcitonin testing was reported to be available at 2/16 (13%) centers, and was not incorporated into any existing CDTs. CONCLUSION: CDTs for the management of febrile young infants are infrequently available among Canadian tertiary paediatric centers, and when present, rarely contain information on newer diagnostic tests. The paucity of CDTs among paediatric academic training centers may in part underlie ongoing practice variation. Heterogeneity among existent CDTs highlights the need for the establishment of updated and unified ED and inpatient national guidelines.